Joint effects of folate and vitamin B12 imbalance with maternal characteristics on gestational diabetes mellitus. Issue 9 (14th February 2019) - Li, Shuying; Hou, Yaxing; Yan, Xinxin; Wang, Yuwen; Shi, Chen; Wu, Xiaoyan; Liu, Huihuan; Zhang, Liwen; Zhang, Xumei; Liu, Juan; Zhang, Ming; Zhang, Qiang; et al.
Abstract: Background: This study examined whether folate and vitamin B12 imbalance is associated with gestational diabetes mellitus (GDM) and explored interactions between B vitamin imbalance and maternal risk factors for GDM. Methods: A cross‐sectional study was performed in 406 Chinese pregnant women. Serum folate, vitamin B12, and blood glucose concentrations were measured at 24 to 28 weeks gestation during GDM screening. A diagnosis of GDM was made based on International Association of Diabetes and Pregnancy Study Groups criteria (fasting plasma glucose [FPG] ≥5.1 mM, 1‐hour plasma glucose ≥10.0 mM, or 2‐hour plasma glucose ≥8.5 mM). Binary logistic regression was used to obtain odds ratios (ORs) after controlling for different confounders. Results: Higher folate levels were associated with higher glucose concentrations and a higher risk of GDM (OR 1.98; 95% confidence interval [CI] 1.00‐3.90), whereas higher vitamin B12 levels were associated with lower FPG and a lower risk of GDM (OR 0.30; 95% CI 0.15‐0.60). A higher folate: vitamin B12 ratio was associated with higher glucose and a higher risk of GDM (OR 3.08; 95% CI 1.63‐5.83). The presence of both a higher folate: vitamin B12 ratio and advanced age further increased the OR to 2.13 (95% CI 1.09‐4.15) with a significant additive interaction. Furthermore, a higher folate: vitamin B12 ratio and a higher prepregnancy body mass index (pp‐BMI) were synergistically associated with an increased risk of GDM (OR 3.03; 95% CI 1.40‐6.57). Conclusions: An imbalance between folate and vitamin B12, represented by a higher folate: vitamin B12 ratio, was highly associated with GDM risk, and this association could be further modified by maternal age and pp‐BMI. Abstract : Highlights Higher folate and lower vitamin B12 levels were associated with higher glucose and a higher risk of gestational diabetes mellitus (GDM). The association between folate and vitamin B12 imbalance and GDM risk can be further modified by maternal risk factors. Abstract : 摘要: 背景: 本研究探讨了叶酸和维生素B12 失衡与妊娠期糖尿病(gestational diabetes mellitus, GDM)之间的关系, 同时进一步研究了B族维生素失衡与母体危险因素交互作用对GDM的影响。 方法: 采用横断面研究的方法, 以406名开展GDM筛查的孕妇为研究对象, 在孕24‐28周检测其血清叶酸、维生素B12 和血糖水平。依据国际糖尿病和妊娠研究协会的标准对GDM进行诊断(空腹血糖[FPG]≥ 5.1 mM, 1小时血糖≥ 10.0 mM, 或2小时血糖≥ 8.5 mM)。采用二元logistic回归分析并获得控制不同混杂因素后的OR值。 结果: 血清中较高的叶酸水平与较高的血糖浓度相关, 且与GDM发生风险增加有关(OR:1.98；95% CI:1.00‐3.90)；而较高的维生素B12 水平与较低的FPG水平相关, 且与GDM发生风险降低有关(OR:0.30；95%CI:0.15‐0.60)。同时较高的叶酸:维生素B12 比值与高血糖和GDM发生风险增加也显著相关(OR:3.08；95% CI:1.63‐5.83)。进一步研究表明, 较高的叶酸:维生素B12 比值与高龄孕妇存在交互作用, 可以增加GDM的发生风险(OR:2.13；95% CI:1.09‐4.15)；且较高的叶酸:维生素B12 比值和较高的孕前BMI也可以协同增加GDM发生的风险(OR:3.03；95% CI:1.40‐6.57)。 结论: 叶酸和维生素B12 失衡(以较高的叶酸:维生素B12 比值为特征)与GDM发生风险增加密切相关, 且孕妇年龄和孕前BMI可以进一步影响二者之间的关系。